A clinical case of spontaneous coronary artery dissection in a young patient - M. K. Akhverdieva; E. V. Khorolets; S. V. Shlyk; R. V. Sidorov; I. V. Ivanov; I. A. Malozemova; V. A. Novak; S. S. Otrutsky; I. A. Udovenko (Klinicist, 2024)
Аim. To describe a clinical case of acute myocardial infarction in a young patient caused by spontaneous dissection of the coronary artery.Material and methods. The patient, a 32-year-old man, was hospitalized in the cardiology department with a clinical picture of acute coronary syndrome. When collecting anamnestic data, it was established that the patient has an aggravated cardiovascular, hereditary, pharmacological anamnesis and concomitant pathology. A special attitude of the patient to hisdisease in the form of an anosognosic reaction was revealed. The data of the coronary angiography study determined further tactics of patient management at the inpatient stage.Results. Taking into account the clinical picture, the dynamics of electrocardiograms, the results of laboratory diagnostics, acute myocardial infarction with ST segment elevation on the electrocardiogram was preliminarily diagnosed. During coronary angiography, spontaneous coronary artery dissection was detected in the patient, which was the main cause of acute left ventricular myocardial infarction. A decision was made to implant 3 stents in order to completely cover the dissection zone of the anterior interventricular branch of the left coronary artery. The choice of conservative and/or surgical tactics for managing patients with spontaneous coronary artery dissection is debatable. After percutaneous coronary intervention, drug therapy was prescribed, including dual antiplatelet therapy. The patient noted an improvement in his well-being, without relapses of pain syndrome. In the dynamics of inpatient treatment, according to echocardiographic examination, an aneurysm of the apex of the left ventricle with a mural thrombus was detected, which required correction of drug therapy, taking into account the increased risks of thromboembolic and hemorrhagic complications.Conclusion. This clinical case demonstrates that spontaneous dissection of the coronary artery is one of the pathogenetic mechanisms of the formation of the clinical picture of acute coronary syndrome and affects the development of complications and further prognosis.